A service ecosystems perspective to explore social prescribing value co-creation for vulnerable young people in NEET situation - Isabel Farina; Daniela Sangiorgi; Cristina Masella; Ilaria Simonelli; Regina Alves; Maria J. Marques; Sonia Dias; Carina Dantas; Sabrina Herzog; Sara Paternoster; Emanuele Torri; Marcello Bertotti (BMC Health Services Research)
Abstract Background Social prescribing inherently embodies a co-productive nature, particularly within the ‘holistic’ model facilitated by the pivotal role of Link Workers. Most attention is focused on collecting evidence about the micro-level relationship between Link Workers and their clients. However, little is known about how this co-productive relationship influences or is influenced by value co-creation at different levels, given the involvement of multiple actors in delivering the intervention. To advance research on the operational processes underlying social prescribing, we propose a conceptual framework utilizing the Service Ecosystems perspective to investigate the application of social prescribing with young people in NEET situations in Italy. Methods A single case study was conducted as part of the European C.O.P.E. (Capabilities, Opportunities, Places, and Engagement) initiative, examining the implementation of social prescribing targeting young NEETs (Not in Education, Employment, or Training) in Italy. Semi-structured interviews were conducted with 27 participants, including six members of the C.O.P.E. coordination team, six Link Workers, and 15 young people aged 15–34 years. Results Findings are presented showing the ecosystem dynamics at each intervention phase: the referral process, co-production of an individualized action plan, and connection with and activation of community assets. Discussion This research illustrates how social prescribing is not a linear path but rather a complex intervention with multiple interacting elements across ecosystem layers. The dyadic relationship between Link Workers and clients operates within broader care services, fostering continuity of care. The service ecosystem perspective offers a valuable framework for examining the dynamic interactions between actors and understanding how their resource integration processes and institutional arrangements foster the emergence of opportunities to support an invisible and hard-to-reach target group, such as young people in NEET situations.